Spatial variation of bat diversity between three floodplain-savanna ecosystems of the Colombian Llanos - Morales Martínez, Darwin M.; Rodríguez-Posada, Miguel E.; Fernández-Rodríguez, Camilo; Calderón Capote, María Camila; Gutierrez Sanabria, Diego Rolando (Therya, 2018)
The ecology of bat assemblages in savanna ecosystems is poorly known. Studies on this subject are scarce in the Colombian Orinoquía; some authors have argued that this region shows a low diversity of bat species relative to other natural regions of Colombia, which contrasts with reports for other Neotropical savannas. In order to broaden the knowledge about bat assemblages in savanna ecosystems in Colombia, we evaluated the alpha (local) and beta (species turnover) diversities in three savanna ecosystems located in Colombian alluvial flood plains of Orinoco Llanos , as compared to other natural regions of Colombia. We sampled bat assemblages across three alluvial floodplain savannas: E1) Mosaic of floodplain savannas and floodplain forests covering less than 20 % of the original area. E2) Dense high forest growing on the flood plains of Whitewater Andean rivers. E3) Aeolian savannas. Mist nets were used in the understory in all cases. We evaluated the representativeness of samples using the Jackknife 1 estimator. The species richness found was compared with the one reported in representative inventories of other natural regions of Colombia. Differences in alpha diversity between the three ecosystems studied were explored by comparing rank-abundance curves and three true-diversity values (q0, q1 and q2). Finally, we evaluated the species turnover across ecosystems using the Jaccard similarity index. A total of 50 bat species were recorded at the regional level, and between 32 and 39 species in each of the ecosystems, representing a greater or similar richness vs other natural regions of Colombia. Sampling representativeness was higher than 80 %. Although no differences were observed in terms of species richness (q0) between localities, differences were evident in the structure of assemblages (q1, q2). Finally, the species turnover between localities was high, with similarity values between 57 % and 64 %. The species richness recorded in the assemblages studied here is similar to that reported for bat assemblages in other natural regions of Colombia, where a higher diversity has been presumed. The differences observed in the structure of abundances of the assemblages studied here may be associated with ecosystem heterogeneity in the Llanos region, characterized by different types of vegetation structure in the various types of forest. In addition, there may be a negative effect of the degree of transformation of natural ecosystems on bat richness and diversity. On the other hand, the high degree of bat species turnover may stem from differences in the composition and structure of riparian forests coupled with the strong seasonality of precipitation in the region, as reported for other Neotropical savannas.